HUBUNGAN KONSENTRASI PM2,5 UDARA DALAM KAMAR SANTRI DENGAN KELUHAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA SANTRI DI PONDOK PESANTREN PPTQ AHMAD DAHLAN PONOROGO - Amalia Neriza, Rizki; Indria Prasasti, Corie (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
Indoor air quality (IAQ), specifically PM2.5 concentration, is an environmental factor that potentially influences the incidence of Acute Respiratory Infections (ARI). Islamic boarding schools, as densely populated living environments, are prone to poor air quality due to high occupancy, limited ventilation, and inadequate hygiene practices. This study aimed to analyze the relationship between PM2.5 concentrations in students' rooms and ARI complaints among students at the PPTQ Ahmad Dahlan Islamic Boarding School in Ponorogo. This was an observational analytic study with a cross-sectional design. The sample consisted of 137 students, selected using the Taro Yamane formula (e=5%) from a total population of 209 students. PM2.5 measurements were conducted in 15 rooms—with each measurement replicated twice—using an Indoor Air Quality Detector over a 60-minute period, with readings recorded every 5 minutes. The results were compared against the quality standards set by the Minister of Health Regulation No. 2 of 2023 (25 µg/m³). Data were analyzed using the Pearson Chi-Square test (α=0.05). A total of 70.1% of students (96/137) reported ARI complaints within the last three months. PM2.5 concentrations exceeded the standard in 79.6% of the rooms (affecting 109/137 students). The Pearson Chi-Square test yielded a p-value of 0.774 (p>0.05), indicating no significant relationship between PM2.5 exposure and ARI complaints. Although PM2.5 concentrations in the majority of students' rooms exceeded the quality standards, there was no statistically significant association between PM2.5 exposure and ARI complaints. These findings suggest that other factors—such as occupancy density, hygiene practices, and individual immune status—play a more dominant role in determining the risk of ARI within the Islamic boarding school environment.